A Test Run on the Impact of Wealth Taxes on Economic Growth in South Africa: The Way Forward: Array - Nemalili, Veronica; Robinson, Zurika (Acta Universitatis Danubius. Œconomica, 2021)
This paper investigates the effects of wealth taxes on the South African economy by analysing the relationship between wealth taxes and Gross Domestic Product (GDP). The Engle and Granger cointegration technique on annual tax data of the current forms of wealth being taxed (donations tax, transfer duty and estate duty), to determine the empirical relationship between wealth taxes and GDP is considered. In conclusion, the study suggests that wealth tax increases GDP in the long run, with no impact in the short-run. If the government introduces additional forms of wealth tax, this change may negatively affect short run changes in GDP. The proposed wealth tax is a continuous annual tax and will therefore cause individuals to make changes to their economic activities. It is believed that the introduction of a comprehensive wealth tax in South Africa by government would not yield favourable results and is thus not to be recommended.